COMPENSATION FOR DAMAGE CAUSED BY A CRIME IN PRE-TRIAL PROCEEDINGS IN CRIMINAL CASES: ISSUES OF THEORY AND PRACTICE - Ivanov, Dmitriy; Tokareva, Ekaterina; Shepeleva, Olga; Chasovnikova, Olga; Stacyuk, Denis (Revista Inclusiones, 2020)
Authors pay close attention to the problems of compensation for damage caused by a crime in pretrial proceedings in criminal cases. The relevance of the subject, as stressed by the authors, is the presence of these problems in Russian legal doctrine, which requires rethinking of approaches, used when creating uniform models for this activity regulation and also the need for a unified approach to the implementation of activities on compensation of harm caused by the crime, from the practical organs. Taking into account the array of all the circumstances, the authors determined the direction of the study and formulated its main problem – is the pre-trial procedure for compensation for damage caused by a crime, integrated into the procedural activities of investigators, interrogators, a set of regulations that can effectively regulate the issues of ensuring compensation for damage caused by a crime? The purpose of this study is to justify and develop provisions that determine theoretical and legal basis for pre-trial compensation for harm caused as a result of criminal acts, an effective mechanism that regulates activities of officials conducting preliminary investigations to compensate for harm caused, as well as proposals for making conceptual changes and additions to the criminal procedure law